ECVD-20 visual ergonomics: A novel tool for evaluating environmental conditions based on visual ergonomics for display users. - Dehghan, Habibollah; Esmaeili, Reza; Mousavifard, Zahrasadat; Jalali, Mahdi; Heidari, Zahra; Esmaeili, Sayed Vahid (Work, 2026)
Background: The growing psychophysical challenges related to display use in workplaces highlight the need for reliable visual ergonomic assessment tools. Objective: This study aimed to develop and validate the Evaluating Environmental Conditions Based on Visual Ergonomics (ECVD-20), a novel tool for evaluating visual ergonomic conditions in display-based work environments. Methods: A cross-sectional study was conducted in 2022. The ECVD-20 was developed through a semi-systematic literature review and expert consultation. Structural validity was examined using exploratory factor analysis (EFA). Three trained experts applied the tool in 236 workplaces. An index was created based on item influence coefficients, and its reliability was assessed. Results: The ECVD-20 demonstrated strong validity (content validity ratio (CVR) = 0.865, content validity index (CVI) = 0.946) and acceptable internal consistency (Cronbach's α = 0.644). The EFA revealed a four-factor structure luminance, lighting systems, ergonomic work tools, and working postures, explaining 55.58% of variance. The receiver operating characteristic (ROC) analysis established a cutoff score of 31.01, effectively classifying total score of ECVD-20 into requires corrective action and no action needed categories. Conclusions: The ECVD-20 indicates good validity and reliability for assessing visual ergonomics across diverse settings. Its practical application can guide interventions to improve workplace health and productivity.